Wire Arc Additive Manufacturing of Aluminium 5356 Alloy: Process Parameter Optimization and Structure-Property Analysis - K. Saravanakumar; J. Nampoothiri; M.R. Prat heesh Kumar (Archives of Metallurgy and Materials)
Wire Arc Additive Manufacturing (WAAM) is an emerging technology in the manufacturing sector, offering benefits such as increased production rates and cost efficiency. This study investigates the WAAM of aluminium alloy 5356, deposited on aluminium 6082 base plates. Key process parameters – arc current, stick-out distance, and travel speed – were optimized using an L9 orthogonal array to improve the quality of multi-wall structures. The optimized parameters facilitated the construction of multi-wall structures using a zig-zag pattern. Microstructural and mechanical properties were analyzed using scanning electron microscopy, tensile testing, and Vickers hardness testing. The results revealed significant differences in grain structure, with coarse grains in the top region and finer grains in the bottom, influenced by varying solidification rates. Additionally, the optimized parameters reduced the occurrence of cracks and pores.